2021
DOI: 10.4103/joacp.joacp_39_19
|View full text |Cite
|
Sign up to set email alerts
|

Failure rate of labor epidural

Abstract: Context: Frequent use of labor epidural has also led to a corresponding increase in failed epidural analgesia (FEA). Aims: This study aims to identify the overall rate of FEA and evaluate its association with trainee anesthesiologist at different years/levels of anesthesia residency training. Settings and Design: Prospective observational study was conducted for one year in the labor room suit of a university hospital. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The plethora of guidance tools currently under development may help to facilitate nerve block administration in emergency settings, lowering the level of experience needed to perform the procedure successfully. 38,39 We believe that needle-based PS-OCT has a high potential to be miniaturized and could be of value also in scenarios where the form factor must be small. As a step toward this goal, we have demonstrated that a simple probe without any scanning or focusing optics is sufficient for layer identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plethora of guidance tools currently under development may help to facilitate nerve block administration in emergency settings, lowering the level of experience needed to perform the procedure successfully. 38,39 We believe that needle-based PS-OCT has a high potential to be miniaturized and could be of value also in scenarios where the form factor must be small. As a step toward this goal, we have demonstrated that a simple probe without any scanning or focusing optics is sufficient for layer identification.…”
Section: Discussionmentioning
confidence: 99%
“…proposed an optical measurement of the force applied to the tip of the needle as it passes through each layer using a fiber-Bragg grating 36 , 37 and work is currently ongoing to create a biocompatible version of this probe. The plethora of guidance tools currently under development may help to facilitate nerve block administration in emergency settings, lowering the level of experience needed to perform the procedure successfully 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation